The complete chloroplast genome sequence of Trapa incisa Sieb. & Zucc. (Lythraceae) - Wang, Wuchao (Mitochondrial DNA B Resour, 2021)
Trapa L., an annual floating-leaved herb, is widely distributed in the old world and has important edible and medicinal values. However, the taxonomy and phylogeny of Trapa are unclear. Here, we reported the complete chloroplast genome of a wild species with small nuts, T. incisa. The complete chloroplast genome size of T. incisa was 155, 453 bp, consisting of two inverted repeat (IR) regions (24, 388 bp), one large single copy (LSC) region (88, 398 bp) and one small single copy (SSC) region (18, 279 bp). A total of 129 genes were annotated, including 83 protein-coding genes, 38 tRNA genes and 8 rRNA genes. Among them, 19 genes were duplicated (6 protein-coding genes, 9 tRNA genes and 4 rRNA genes). The phylogenomic analysis suggested a close relationship between T. incisa and T. maximowiczii.